Targeting Microglial α-Synuclein/TLRs/NF-kappaB/NLRP3 Inflammasome Axis in Parkinson’s Disease - Li, Yunna; Xia, Yun; Yin, Sijia; Wan, Fang; Hu, Junjie; Kou, Liang; Sun, Yadi; Wu, Jiawei; Zhou, Qiulu; Huang, Jinsha; Xiong, Nian; Wang, Tao (Frontiers in Immunology, 2021)
According to emerging studies, the excessive activation of microglia and the subsequent release of pro-inflammatory cytokines play important roles in the pathogenesis and progression of Parkinson's disease (PD). However, the exact mechanisms governing chronic neuroinflammation remain elusive. Findings demonstrate an elevated level of NLRP3 inflammasome in activated microglia in the substantia nigra of PD patients. Activated NLRP3 inflammasome aggravates the pathology and accelerates the progression of neurodegenerative diseases. Abnormal protein aggregation of α-synuclein (α-syn), a pathologically relevant protein of PD, reportedly activates the NLRP3 inflammasome of microglia through interaction with toll-like receptors (TLRs). It eventually releases pro-inflammatory cytokines through the translocation of nuclear factor kappa-B(NF-κB) and impairment of mitochondria, thus damaging the dopaminergic neurons. Currently, therapeutic drugs for PD are primarily aimed at providing relief from its clinical symptoms, and there are no well-established strategies to halt or reverse this disease. In this review, we aimed to update existing knowledge on the role of the α-syn/TLRs/NF-κB/NLRP3 inflammasome axis and microglial activation in PD. In addition, this review summarizes recent progress on the α-syn/TLRs/NF-κB/NLRP3 inflammasome axis of microglia as a potential treatment for PD by inhibiting microglial activation.